Randomized Trial of Vaginal Prostaglandin E2 Versus Oxytocin for Labor Induction in Term Premature Rupture of Membranes - Cigdem Kunt; Mine Kanat-Pektas; Ayse Nur Cakir Gungor; Raziye Keskin Kurt; Mustafa Ozat; Cavidan Gulerman; Tayfun Gungor; Leyla Mollamahmutoglu (Elsevier, 2010)
Objective: The aim of this study was to compare the efficacy and safety of a prostaglandin E2 (PGE2) vaginal insert with those of oxytocin for labor induction. The present study also examined whether its use reduces the rate of cesarean delivery in term pregnancies with premature rupture of membranes (PROM) and low Bishop scores. Materials and Methods: A total of 240 women with singleton pregnancies at ≥ 37 weeks, no prior uterine scar, vertex presentations, reactive nonstress tests, PROM for ≥ 12 hours and Bishop scores of ≤ 6 were randomly assigned to receive either oxytocin or vaginal PGE2. The primary outcomes were time from induction to delivery and mode of delivery. Results: The time from labor induction to active labor onset was significantly shorter in the oxytocin group than in the PGE2 group (4.9 ± 4.1 vs. 8.5 ± 3.6 hours; p = 0.02). The time from induction to delivery was also significantly shorter in the oxytocin group (3.4 ± 1.5 vs. 9.6 ± 4.7 hours; p = 0.02). Cesarean delivery rates were statistically similar in the oxytocin and PGE2 groups (18.3 vs. 20.0%; p = 0.81). Neonatal outcomes were comparable in both groups. Comparable results were observed for nulliparous women included in the study population. Conclusion: Oxytocin treatment seems to be superior to vaginal administration of PGE2 to induce labor in term pregnancies complicated with PROM and unfavorable services.